HUBUNGAN INTELEGENSI DAN MOTIVASI DENGAN PRESTASI BELAJAR MAHASISWA S1 KEPERAWATAN STIKES YAYASAN RS ISLAM SURABAYA - Kartini, Yanis (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2013)
There are many factors which affect the academic achievement: internal and external factors. The internal factors include the physical and psychological factors (interest, intelligence, motivation, attention, readiness, and maturity). In academic year of 2011/2012, STIKes Yarsis has added one test, the psychological test, to determine the candidates to pass the student’s admission test. So far, the data haven’t been managed as the important information for the educational management. Therefore, the purpose of this study was to find out the bivariate and multivariate correlation between intelligence and motivation toward the student’s academic achievement. The design of study was analytic-cross sectional. The population involved the students of Program of Study of S-1 in the academic year 2011/2012. 106 respondents were chosen as the samples by using simple random sampling technique. The independent variable was the level of intelligence and motivation, whereas the dependent variable was the academic achievement. The data collection was done by using secondary data, which were then analyzed by using simple and multiple linear regression tests. The result of study in bivariate correlation analysis showed that there was a correlation between intelligence and motivation toward the student’s academic achievement. The independent variable playing a role in predicting the GPA (grade-point average) was motivation (p = 0.028). The value of R-Squared was 0.045 which meant that 4.5% of the academic achievement was affected by motivation, whereas the rest of them were affected by other factors. Moreover, the result of analysis described that GPA = 3.097 + 0.060 * motivation. In conclusion, in bivariate correlation analysis, intelligence and learning motivation had a correlation with academic achievement. In multivariate correlation analysis, intelligence didn’t have any correlation with academic achievement, whereas motivation had correlation with academic achievement. Furthermore, academic achievement had a relationship with motivation (4.5%), and the rest of them had a correlation with other factors, such as campus environment, learning media, curriculum, lecturers, social support, etc